Measurement of the Effective Weak Mixing Angle in p p →z /γ∗ →+- Events - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2018)
We present a measurement of the effective weak mixing angle parameter sin2θeff in pp→Z/γ∗→μ+μ- events at a center-of-mass energy of 1.96 TeV, collected by the D0 detector at the Fermilab Tevatron Collider and corresponding to 8.6 fb-1 of integrated luminosity. The measured value of sin2θeff[μμ]=0.23016±0.00064 is further combined with the result from the D0 measurement in pp→Z/γ∗→e+e- events, resulting in sin2θeff[comb]=0.23095±0.00040. This combined result is the most precise measurement from a single experiment at a hadron collider and is the most precise determination using the coupling of the Z/γ∗ to light quarks.